Photocatalysis Fundamentals, Materials and Applications - Zhang, Jinlong (Lecture Notes in Chemistry,, 2018)
This book describes the photocatalytic mechanism, factors affecting photocatalytic activity, design and preparation of different kinds of nanostructured photocatalysts, and their applications in the environmental and energy fields. Further, it illustrates a broad range of modification methods including ion-doping, heterojunction, noble metal deposition, morphological control and sensitizations, which are used to extend the light absorption range of photocatalysts and reduce recombination between electrons and holes. Promising applications include water splitting, contaminant decomposition and photocatalytic reduction of CO2, which are closely related to environmental redemption and new energy development. The book offers an intriguing and useful guide for a broad readership in various fields of catalysis, material sciences, environment and energy.